Respostas
respondido por:
1
(2x - 7)/ 5 = (x + 2)/3
3(2x-7) = 5(x + 2)
6x - 42 = 5x + 10
6x - 5x = 42 + 10
x = 52
*-*-*-*-*-*-*-*-*-*-*-*
10/10/2016
Sepauto
*-*-*-*-*-*-*-*-*-*-*-*
3(2x-7) = 5(x + 2)
6x - 42 = 5x + 10
6x - 5x = 42 + 10
x = 52
*-*-*-*-*-*-*-*-*-*-*-*
10/10/2016
Sepauto
*-*-*-*-*-*-*-*-*-*-*-*
respondido por:
1
(2x-7)/5=(x+2)/3
3 (2x-7)=5(x+2)
6x-42=5x+10
6x-5x=42+10
x=52
3 (2x-7)=5(x+2)
6x-42=5x+10
6x-5x=42+10
x=52
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás